2023
DOI: 10.1021/acs.organomet.3c00122
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Mechanisms of Methane, Ethane, and Benzene C–H Amination with an Iodine(III) Bistriflimide Complex

Abstract: The iodine(III) bistriflamide complex (C 6 F 5 ) III I(NTf 2 ) 2 in HNTf 2 (bistriflimide acid; (CF 3 SO 2 ) 2 NH) selectively aminates methane and ethane. At a 100 °C reaction with methane after 3 h, it resulted in the exclusive formation of MeNTf 2 with a yield of approximately 40%. For ethane, at 100 °C in 2 h, a > 80% yield was found for a combination of monofunctionalized and difunctionalized amination products. In contrast to alkanes giving functionalized products, the reaction of (C 6 F 5 )I III (NTf 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… 38 Such activation has only very recently been reported by Periana and co-workers by C 6 F 5 -I(NTf 2 ) 2 on methane and ethane at elevated temperatures and pressures (see next section). 39 We surmised that the intermediate in these reactions was potentially p -NO 2 -C 6 H 4 -I(OTf)(H). To lend support to this hypothesis we reacted p -NO 2 -C 6 H 4 -I(OTf) 2 with adamantane and 1-fluoroadamantane.…”
Section: The Myth and Redemption Of Ari(otf)mentioning
confidence: 99%
See 1 more Smart Citation
“… 38 Such activation has only very recently been reported by Periana and co-workers by C 6 F 5 -I(NTf 2 ) 2 on methane and ethane at elevated temperatures and pressures (see next section). 39 We surmised that the intermediate in these reactions was potentially p -NO 2 -C 6 H 4 -I(OTf)(H). To lend support to this hypothesis we reacted p -NO 2 -C 6 H 4 -I(OTf) 2 with adamantane and 1-fluoroadamantane.…”
Section: The Myth and Redemption Of Ari(otf)mentioning
confidence: 99%
“…Periana and co-workers recently reported the isolation of C 6 F 5 -I(NTf 2 ) 2 , albeit without obtaining a crystal structure. 39 They found that at elevated temperatures and pressures this compound could effect the activation of simple sp 3 C–H bonds in ethane and methane generating the corresponding simple alkyl-NTf 2 compounds. Given the above discussion regarding misidentification of reactive I( iii ) species, we isolated p -NO 2 -C 6 H 4 -I(NTf 2 ) 2 via reaction of p -NO 2 -C 6 H 4 -IF 2 with 2 equivalents of TMS-NTf 2 ( Scheme 12 ).…”
Section: The Myth and Redemption Of Ari(otf)mentioning
confidence: 99%
“…While we were undertaking this study Periana and co-workers isolated and spectroscopically characterized C 6 F 5 –I(NTf 2 ) 2 and showed that at elevated temperatures and pressures direct C–H activation of simple alkanes is possible. 13 They did not however confirm the structure by X-ray crystallography and in light of the previous misidentifications of PhI(OTf) 2 , as well as other recent cases involving structural misassignment of I( iii ) complexes, 14–16 it is important that structural confirmation of ArI(NTf 2 ) 2 is obtained. In this report we structurally characterize NO 2 –C 6 H 4 –I(NTf 2 ) 2 and provide analysis that shows these NTf 2 ligated species are significantly stronger oxidizing agents than NO 2 –C 6 H 4 –I(OTf) 2 , representing the current frontier in the oxidative ability of ArIL 2 and possibly the limit for this class of compound.…”
mentioning
confidence: 92%
“…Periana and co-workers generated C 6 F 5 –I(NTf 2 ) 2 in situ from C 6 F 5 –I(OTFA) 2 and HNTf 2 and were also able to isolate C 6 F 5 –I(NTf 2 ) 2 via a 4-cycle exchange between C 6 F 5 –I(OTFA) 2 and HNTf 2 . 13 We have previously found that TMS metathesis is an efficient one-step procedure for these types of transformations, 11 and examined if this would be effective for generation of NO 2 –C 6 H 4 –I(NTf 2 ) 2 . Reactions of NO 2 –C 6 H 4 –IF 2 and NO 2 –C 6 H 4 –I(OTFA) 2 were carried out with 2 equivalents of TMS-NTf 2 in CDCl 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation